The Role of Culture of Communication in the Formation of Personality (Journal of Pedagogical Inventions and Practices, 2022)
This article describes the role of the culture of communication in the formation of personality, gives practical advice on the forms and means of communication. The ways of proper communication, the specifics of socio-psychological communication are considered